(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Generally, it has been established that games are part of non-formal curriculum and they do complement the formal curriculum. However, in secondary schools, games have been treated as second rate. Methods used in implementing of games programs varies from one school to another because of the varied support given and its value in enhancing academic achievement has not been established. The purpose of this study was to investigate the implementation of games and its contribution to students academic achievement in secondary schools in Rongo Sub- County, Kenya. The objective of this study was to determine methods used in implementing games programs in secondary schools in Rongo Sub-County secondary schools and their effects on academic achievement.The study adopted correlation, survey and ex post facto designs. The target population included 50 games teachers, 50 head teachers and 2000 form four students in 50 schools in Rongo Sub-county that sat for the Rongo Sub-County Examinations in the year 2010. Saturated sampling technique was used to select 46 games teachers and 46 head teachers used in the study. Stratified random sampling technique was used to select 700 form four students who were a divided into two equal groups (n=350) named as experimental group and control group. Students questionnaires, games teachers questionnaires, games teachers interview schedules, head teachers interview schedule and an observation schedule for games facilities were used to collect data. Quantitative data was analyzed using descriptive statistics while qualitative data was received in verbatim form, transcribed and reported according to emerging themes. Findings for the study the study further established that academic achievement had some relationship with the level to which a student participated in games programs. It was recommended that school administrations should provide adequate material and support for implementing games and special attention should be given to the academic wellbeing of participants in games since games do contribute to better academic achievement of students.